PENGARUH BEBAN KERJA, GAYA KEPEMIMPINAN DAN KOMPENSASI MONETER TERHADAP KINERJA KARYAWAN PT BUMI MULIA PERKASA - Jhonson; Iswandi, Mei (Jurnal Gici Jurnal Keuangan dan Bisnis, 2023)
As one of the private companies, PT Bumi Mulia Perkasa burusaha improves the quality of the performance of its employees. The problems are low communication, lack of form of responsibility from employees to workers given by the company, absence of delegation of authority given by the leader to employees so that employees hesitate in making decisions and actions on the work assigned to them, and lack of compensation given by the company to its employees resulting in decreased employee performance. The research method used is quantitative descriptive with the type of research used in the form of data collection using questionnaires. Sample selection is carried out by means of saturated sampling. The sample amounted to 30 respondents, using multiple linear regression analysis. The results of the regression test showed that 53.8% of performance factors could be explained by workload, leadership style and monetary compensation while the remaining 46.2% was explained by other factors not studied in this study. While the results of the F test show that simultaneously the variables workload, leadership style and monetary compensation have a significant effect on performance. The results of the t test showed that leadership style variables and monetary compensation variables had a significant effect on performance, while workload variables did not have a positive and significant effect on performance.